2017
DOI: 10.1002/ijgo.12259
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term incidence of hysterectomy following endometrial resection or endometrial ablation for heavy menstrual bleeding

Abstract: A significant majority of women who underwent ERA for HMB did not require hysterectomy up to 25 years after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Obviously, there are socioeconomic benefits, as hysterectomy is substantially more expensive than TCRE and an improvement in the We included women with referral diagnosis of menorrhagia, metrorrhagia or menometrorrhagia who did not solely suffer from structural abnormalities such as fibromas or polyps, which are shown by several studies to complicate endometrial resections. 9,16,17 Cravello et al observed that reaching and resecting the deepest parts of the fibroma can be nearly impossible, and that fibroma can re-appear inside the uterine cavity, causing the bleeding to restart or continue. 9,16 This was also supported by Hart and Magos, who observed that the presence of fibromas was a risk factor for hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, there are socioeconomic benefits, as hysterectomy is substantially more expensive than TCRE and an improvement in the We included women with referral diagnosis of menorrhagia, metrorrhagia or menometrorrhagia who did not solely suffer from structural abnormalities such as fibromas or polyps, which are shown by several studies to complicate endometrial resections. 9,16,17 Cravello et al observed that reaching and resecting the deepest parts of the fibroma can be nearly impossible, and that fibroma can re-appear inside the uterine cavity, causing the bleeding to restart or continue. 9,16 This was also supported by Hart and Magos, who observed that the presence of fibromas was a risk factor for hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…9,16,17 Cravello et al observed that reaching and resecting the deepest parts of the fibroma can be nearly impossible, and that fibroma can re-appear inside the uterine cavity, causing the bleeding to restart or continue. 9,16 This was also supported by Hart and Magos, who observed that the presence of fibromas was a risk factor for hysterectomy. 17 Our study likewise demonstrated fibromas to be a significant risk factor for a hysterectomy, increasing the odds of this outcome by 143%, corresponding well with the results of the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the present study, follow‐up data until the end of 2015 were obtained using the pathology laboratory report system. The Grampian Region of Scotland has a very stable population, one principal hospital, one pathology service, and a comprehensive cancer database, which facilitates reliable population‐based and long‐term follow‐up studies . The primary outcome was diagnosis of endometrial cancer after EA/R for menorrhagia.…”
Section: Methodsmentioning
confidence: 99%
“…Region of Scotland has a very stable population, one principal hospital, one pathology service, and a comprehensive cancer database, which facilitates reliable population-based and long-term follow-up studies. 18 The primary outcome was diagnosis of endometrial cancer after EA/R for menorrhagia. Secondary outcomes included the EA/R methods used and all non-endometrial cancer indications for hysterectomy after EA/R.…”
Section: Methodsmentioning
confidence: 99%
“…Permission to collect clinical data was given by the National Health Service Grampian Clinical Effectiveness Team (Quality, Governance and Risk Unit, 19th July 2017, reference number 3790). One of the major strengths of Scottish health data is the ability to perform vigorous data linkage in a national population, using Community Health Index (11,12). This allows for reliable population based and long-term follow up studies (12).…”
Section: Methodsmentioning
confidence: 99%